Computed tomography (CT) imaging evaluation of integrated traditional Chinese medicine cooperative therapy in treating acute cerebral infarction: A randomized controlled trial. Issue 18 (May 2020) - Liu, Ruijia; Yu, Xudong; Zhang, Liping; Zhang, Hong; Gong, Yuanyuan; Wu, Kang; Yan, Shuting; Song, Lianying
Abstract: Introduction: Acute cerebral infarction is a clinically common cerebrovascular disease. Acute cerebral infarction is characterized by sudden onset, dangerous illness, high risk of death, and disability. Computed tomography perfusion imaging can detect abnormal brain tissue perfusion 30 minutes after the onset of cerebral ischemia, providing the earliest and most valuable information for clinical diagnosis and treatment. In recent years, the effect of traditional Chinese medicine on acute cerebral infarction has been remarkable. Methods/design: This study plan randomly divided eligible acute cerebral infarction patients into two groups. Patients in the control group will be treated with conventional Western medicine; patients in the intervention group will be treated with traditional Chinese medicine cooperative therapy on the basis of conventional Western medicine. The curative effects will be selected before treatment, 2 weeks after treatment, and 3 months follow-up. The changes in CT imaging evaluation, NIHSS score, and BI index of the two groups of patients will be observed. Discussion: We aim to provide higher evidence-based medical evidence for traditional Chinese medicine treatment of acute cerebral infarction. And clarify the application value of computed tomography perfusion imaging in the diagnosis and efficacy evaluation of acute cerebral infarction. Trial registration: ClinicalTrials.gov, ChiCTR2000030230, Registered on 03 March 2020.